Influence of shielding gases on preheat produced in surface coatings incorporating SiC particulates into microalloy steel using TIG technique. (October 2014) - Patel, P.; Mridha, S.; Baker, T. N.
<x content-type="archive" xml:space="preserve">Abstract</x> The use of a tungsten inert gas (TIG) welding torch has resulted in the development of an economical route for surface engineering of alloys, giving similar results to the more expensive high power laser. Owing to the preheating generated by both techniques, the extent of the temperature rise is sufficient to produce significant changes to the melt dimensions, microstructure and properties between the first and last tracks melted during the coating of a complete surface. The present study examines if similar changes can occur between the start and finish locations of a single track of 50 mm length. The results show that for a TIG melted surface of a microalloy steel substrate, with or without incorporating preplaced SiC particles, in either argon or argon–helium environments, a maximum temperature of 375°C developed in the second third of the track. Even over this short distance, a hardness decrease of >300 HV was recorded in the resolidified SiC coated substrate melt zone, microstructure of a cast iron with cracks was observed. In addition, porosity was found in all the tracks, with and without preplaced SiC powders.